Synergies and tensions between universal health coverage and global health security: why we need a second ‘Maximizing Positive Synergies’ initiative - Ooms, Gorik; Hanefeld, Johanna; Jahn, Albrecht (BMJ global health, 2017)
A kind of courtship is going on between proponents of universal health coverage (UHC) and proponents of global health security (GHS). In our opinion, efforts to make progress on the path to UHC and efforts to improve GHS can be synergistic, but are not self-evidently so. Making this partnership work will require careful thinking and planning. Several comments on ‘lessons from Ebola’ highlight the potential of UHC as a way to improve GHS.1 Simon Rushton, Louis Lillywhite and Bhimsen Devkota argue that the “[p]romotion of health security therefore entails ensuring that effective health systems exist before a crisis, are sustained during and after conflict and disaster, and are at all times accessible to the population.”1 Rob Yates, Ranu Dhillon and Ravi Rannan-Eliya remind us that several epidemics of global concern ‘occurred in settings without universal health coverage where health systems were unable to perform effective public health functions’.1 In a reaction to these ‘lessons from Ebola’, and a preview to the G7 summit in Ise-Shima of May 2016, Gavin Yamey argued that a way to make the case for UHC more compelling ‘could be to link UHC to the worldwide concern about pandemics in the wake of the Ebola crisis’,2 and he encouraged Japan—a longstanding proponent of UHC and GHS-to ‘rouse the G7 nations into action on universal health coverage’.2 Japan indeed promoted UHC and GHS, as an ‘inseparable couple’,3 and the ‘G7 Ise-Shima Vision for Global Health’ outcome document highlights both.4 ### Not a new attempt to create an alliance The present courtship is not new. The 2007 World Health Report, on ‘A safer future: global public health security in the 21st century’,5 highlighted the importance of strong health systems to enhance GHS. Without using the expression UHC, this report tried to tie efforts to make progress towards UHC into …